The Development of Security System for Sharing CAD Drawings in u-Environment - Chang, Hangbae; Kim, Kyung Kyu; Kim, Yeongdeok (Computing and Informatics, 2012)
Because most CAD drawings are composed of a collection of files with various extensions, there exist problems associated with the processing speed and the accuracy of CAD files encryption (decryption) using file based secure methods. In this study, an innovative system of securing CAD files based on the workplace against illegal piracy of design knowledge in ubiquitous environment is presented. The proposed technology is to store all design files in the secure workplace which can be accessed by the authorized users and design applications only using Application Programming Hooking at user level and System Service Table at kernel level. The technology is demonstrated in this paper using its implementation example in an automobile company to verify it and CAD files can be shared among users without a concern of its leakage to the competitors by internal user.